2020
DOI: 10.3390/polym12071586
|View full text |Cite
|
Sign up to set email alerts
|

Master Curve Establishment and Complex Modulus Evaluation of SBS-Modified Asphalt Mixture Reinforced with Basalt Fiber Based on Generalized Sigmoidal Model

Abstract: Basalt fiber has been proved to be a good modified material for asphalt mixture. The performance of basalt fiber modified asphalt mixture has been widely investigated by extensive researches. However, most studies focused on ordinary static load tests, and less attention was paid to the dynamic mechanical response of asphalt mixture incorporating with basalt fiber. This paper aims to establish the master curve of complex modulus of asphalt mixture incorporating of styrene-butadiene-styrene (SBS) polymer and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Based on the traditional Williams-Landel-Ferry (WLF) equation, the shift factor ( α T ) can be obtained as shown in the Equation (6) [ 48 , 50 ]. in which p 1 and p 2 represent fitted terms, T 0 is the reference temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the traditional Williams-Landel-Ferry (WLF) equation, the shift factor ( α T ) can be obtained as shown in the Equation (6) [ 48 , 50 ]. in which p 1 and p 2 represent fitted terms, T 0 is the reference temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this, the measured dynamic modulus of bituminous mixture in dynamic modulus test at various test conditions can be converted into the values at the reference temperature using the shift factor, thereby forming a smooth master curve of dynamic modulus. Therefore, the viscoelastic behavior of bituminous concretes in a larger temperature and frequency interval would be forecasted according to the master curve of dynamic modulus [ 48 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is also found that all asphalt mixtures showed similar trends regardless of modifier types. According to many studies [ 27 , 42 , 43 , 46 , 66 , 67 , 68 , 69 , 70 ], polymer modification resulted in a higher modulus for the modified asphalt mixture as compared with the control asphalt mixture. In this study, similar behavior was found by using different polymers, where the dynamic modulus of asphalt mixtures improved due to polymer addition.…”
Section: Resultsmentioning
confidence: 99%
“…In the DSR test, the dynamic viscoelastic behavior of bitumen can be divided into two parts, including G * and δ [4,51,52]. G * is calculated by applying dynamic shear stress (τ max ) to bituminous sample, c max , defined by…”
Section: Dynamic Shear Rheometermentioning
confidence: 99%